Numerical modelling of fibre composites with random-elastic components - Kamński, Marcin; Gajl, Olaf (Computer Assisted Methods in Engineering and Science, 2023)
An original idea of the Stochastic Finite Element Method (SFEM) application in numerical modeling of random fluctuations of elastic properties of fibre composites components has been presented in this paper. The displacement and the stress random fields have been analysed for various contents of a fibre periodicity cell of such a composite, and for different coefficients of variation of the Young modulus of both phases.